2016
DOI: 10.1111/hel.12295
|View full text |Cite
|
Sign up to set email alerts
|

Surface Antigen Profiling of Helicobacter pylori‐Infected and ‐Uninfected Gastric Cancer Cells Using Antibody Microarray

Abstract: This study suggests the tolerance of immune system toward tumor cells in gastric cancer and distinct mechanisms of immune responses exploited by different H. pylori strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Capture of single cell suspension of gastric epithelial cells onto DotScan TM slides has been described in previous study (Sukri et al 2016). The slides consist of more than 140 CD antibodies against CD antigens that have been customized to consist 82 established CD antibodies against T-, B-, and myeloid cells and another 42 CD antibodies were selected markers of gastric cancer cells and Helicobacter pylori infection (MedSaic Pty.…”
Section: Capturing Single Cell Suspension Of Gastric Epithelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Capture of single cell suspension of gastric epithelial cells onto DotScan TM slides has been described in previous study (Sukri et al 2016). The slides consist of more than 140 CD antibodies against CD antigens that have been customized to consist 82 established CD antibodies against T-, B-, and myeloid cells and another 42 CD antibodies were selected markers of gastric cancer cells and Helicobacter pylori infection (MedSaic Pty.…”
Section: Capturing Single Cell Suspension Of Gastric Epithelial Cellsmentioning
confidence: 99%
“…DotScan TM array employs more than 140 clusters of differentiation (CD) antibodies on one slide for profiling of many CD antigens in a single assay. Current DotScan TM antibody microarray consists of 82 CD antibodies against established CD antigens (T and B cells markers and myeloid cell markers) and 40 CD antibodies selected against specific disease that can be customized (Sukri et al 2016). CD antigens are cell surface molecules expressed mainly on leukocytes and other cells that are important in immune responses (Zhou et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helicobacter pylori is a pathogen that colonizes roughly one half of the world’s population which causes chronic gastritis. Sukri et al [ 40 ] employed the DotScan™ antibody microarray to determine the tolerance of immune system toward tumor cells in gastric cancer using 144 CD antibodies to profile the distribution of CD markers between Helicobacter pylori infected and un-infected gastric adenocarcinoma cells. Interestingly, they found gastric adenocarcinoma cell line AGS infected by cagA + H. pylori showed increased CD27 expression, which is essential for maintenance of T cell population, and increased CD markers were also detected in H. pylori -infected gastric cancer patients.…”
Section: Recent Applications (Since 2011)mentioning
confidence: 99%
“…Based on these studies, an antibody microarray was successfully applied for the quality control of mesenchymal stem cells . Other research groups also reported the potential use of similar antibody microarrays in immunophenotyping. …”
Section: Introductionmentioning
confidence: 99%